The Relationship of Shoulder Flexibility to Swimming Speed in Teenage Beginner Swimmers - Ni Nyoman Ayu Mellynia Putri Astawa; I Putu Darmawijaya; Luh Putu Ayu Vitalistyawati (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
One of the improved physical components in juvenile novice swimmers is the speed of swimming. Swimming speed can be affected by several factors one of the factors is the flexibility of the shoulders. This study aims to determine the relationship between shoulder flexibility and swimming speed in adolescent novice swimmers in Club Renang Takahide, Badung Regency, Bali.  The research design used was cross sectional and a sample of 10 people was obtained. In this study, there was a free variable, namely shoulder flexibility and the bound variable, namely swimming speed. Data collection for shoulder flexibility was measured using a shoulder elevation test, while swimming speed was measured with a digital stopwatch.  Based onthe calculation results using the Pearson Product Moment correlation test with a value of 0.001 and a very strong correlation of -0. 875. This suggests the presence of a very strong correlation in a significant negative direction between shoulder flexibility and swimming speed in teenage novice swimmers. The swimming speed with the shoulder flexibility category is less good is slower compared to the very good shoulder flexibility category.